Rate of Malignancy in the Complex Renal Cystic Lesions (Bosniak Iif, Iii, Iv) Single Center Study - Syed Rafi Uddin Shah, Jamal Muustafa Khan, Hafiz Dur E Furqani, Mehnaz Jabeen, Pardeep Kumar Maheshwari, Altaf Hashmi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the rate of malignancy in the complex renal cystic lesions. Material and methods: We studied 111 patients both male and female above the age of 18 years with complex renal cystic lesions classified as Bosniak category IIF, III, and IV on CT. Patients with Bosniak categories I and II were excluded from the study. The rate of malignancy was analyzed. Results: The mean age of the patients was 47.58±15.05 years. 27% of patients were Bosniak category IIF, 29.7% of patients were category III and 43.2% were category IV. The overall rate of malignancy was 62.2% in all patients who presented with complex renal cystic lesions. The rate of malignancy in Bosniak categories IIF,III and IV were 33.3%, 54.5% and 85.4% respectively. Conclusion: Malignancy was observed in 62.2% of the patients who presented with complex renal cystic lesions. The rate of malignancy in Bosniak categories IIF,III and IV were 33.3%, 54.5% and 85.4% respectively. Keywords: Malignancy, Renal cysts, Bosniak classification